2021
DOI: 10.1177/1550147720986116
|View full text |Cite
|
Sign up to set email alerts
|

Identification of crack development in granite under triaxial compression based on the acoustic emission signal

Abstract: To explore the development mechanism of cracks in the process of rock failure, triaxial compression tests with simultaneous acoustic emission monitoring were performed on granite specimens using the MTS rock mechanics test system. The frequency-domain information of the acoustic emission signal was obtained by the fast Fourier transform. The Gutenberg–Richter law was used to calculate the acoustic emission signals and obtain the b-value dynamic curve in the loading process. Combined with the stiffness curve of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…Final failure patterns of granite samples subjected to different thermal shock treatments under triaxial compression are presented in Figure 11. When the temperature is at 25 °C, the angle of the main macroscopic fracture with respect to the horizontal direction is about 60 °, as shown in Figures 11(a Water cooling (5 Mpa) Yan Qin et al [34] Naturally cooling (10 Mpa) Xu et al [35] Fitting curve 8 Geofluids heterogeneous distribution and the thermal stress in minerals (tensile) under rapid quenching. At failure, there are many large-angle macroscopic tensile fractures, which is due to the decrease of tensile resistance with the increase of temperature [37].…”
Section: Failure Patternmentioning
confidence: 99%
“…Final failure patterns of granite samples subjected to different thermal shock treatments under triaxial compression are presented in Figure 11. When the temperature is at 25 °C, the angle of the main macroscopic fracture with respect to the horizontal direction is about 60 °, as shown in Figures 11(a Water cooling (5 Mpa) Yan Qin et al [34] Naturally cooling (10 Mpa) Xu et al [35] Fitting curve 8 Geofluids heterogeneous distribution and the thermal stress in minerals (tensile) under rapid quenching. At failure, there are many large-angle macroscopic tensile fractures, which is due to the decrease of tensile resistance with the increase of temperature [37].…”
Section: Failure Patternmentioning
confidence: 99%
“…Damaskinskaya et al [10] analyzed the spatial distribution of hypocenters of AE signal sources, and revealed that the transition to correlated defect formation occurs in some regions in the case of continuous electrical exposure, despite the accumulation of almost uniform spatial defect. Wang et al [11] explored the development mechanism of cracks in the process of rock failure using AE and found that by fully analyzing the characteristics of AE signals in the time and frequency domain, the time and conditions of producing large cracks can be accurately and efficiently determined. Although extensive research has been conducted on the evolution characteristics of spatial fractures based on AE, all fractures are considered as a whole, and there is little research on fracture clusters.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic of the quiet period was that only a small amount of acoustic emission signals are distributed in the specimens at this stage. Wang et al [3] carried out triaxial compression tests on granite samples under real-time AE monitoring. It was found that the AE signals of granite samples under triaxial compression can be divided into four stages: quiet period 1, active stage 1, quiet period 2, and active stage 2.…”
Section: Introductionmentioning
confidence: 99%